Prevalence of chronic obstructive pulmonary disease in China - A large, population-based survey - Zhong, Nanshan; Wang, Chen; Yao, Wanzhen; Chen, Ping; Kang, Jian; Huang, Shaoguang; Chen, Baoyuan; Wang, Changzheng; Ni, Diantao; Zhou, Yumin; Liu, Shengming; Wang, Xiaoping; et al. (美国呼吸道与危重症监护医学杂志, 2007)
Rationale: The prevalence of chronic obstructive pulmonary disease (COPD) in China is largely unknown. Objectives: To obtain the COPD prevalence in China through a largepopulation, spirometry-based, cross-sectional survey of COPD. Methods: Urban and rural population-based cluster samples were randomly selected from seven provinces/cities. All residents 40years of age or older in the selected clusters were interviewed with a standardized questionnaire revised from the international BOLD (Burden of Obstructive Lung Diseases) study. Spirometry was performed on all eligible participants. Patients with airflow limitation (FEV1/FVC < 0.70) were further examined by post-bronchodilator spirometry, chest radiograph, and electrocardiogram. Post-bronchodilator FEV1/ FVC of less than 70%was defined as the diagnostic criterion of COPD. Measurements and Main Results: Among 25,627 sampling subjects, 20,245 participants completed the questionnaire and spirometry (response rate, 79.0%). The overall prevalence of COPD was 8.2% (men, 12.4%; women, 5.1%). The prevalence of COPD was significantly higher in rural residents, elderly patients, smokers, in those with lower body mass index, less education, and poor ventilation in the kitchen, in those who were exposed to occupational dusts or biomass fuels, and in those with pulmonary problems in childhood and family history of pulmonary diseases. Among the patients who had COPD, 35.3% were asymptomatic; only 35.1 % reported lifetime diagnosis of bronchitis, emphysema, or other COPD; and only 6.5% have been tested with spirometry. Conclusions: COPD is prevalent in individuals 40 years of age or older in China. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000250136400007&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Critical Care Medicine Respiratory System SCI(E) 237 ARTICLE 8 753-760 176